Investigation of biochemical blood parameters, characteristics for carcass, and mineral composition in chicken meat when feeding on coriander seed and rosemary leaves - Jameel, Firas R (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: Investigating the antibiotic and antioxidant benefits of medicinal herbs to enrich the serum immune responses of chicken meat. Materials and Methods: A total of 1,080 Ross 308 broilers were reared up to 42 days. The broilers were divided randomly into nine assemblies, with each sectioned into three replicates. The first and second were supplemented with 0.25% and 0.50% of coriander seeds, respectively, while the third and fourth with 0.25% and 0.50% of rosemary leaves, respectively. A mixture of herbs from the two plants were added to fifth, sixth, seventh, and eighth treatments [(0.50% coriander seeds + 0.50% rosemary leaves), (0.25% coriander seeds + 0.50% rosemary leaves), (0.50% coriander seeds + 0.25% rosemary leaves), and (0.25% coriander seeds + 0.25% rosemary leaves)], respectively, whereas chicks in the ninth as a control group. Results: The results showed the pH for the thigh and breast of the carcass were measured. Glycogen levels, serum immunity (H, L, Hlration, Albumin, Globulin, and A/G ratio at 28 days and alanine aminotransferase, aspartate aminotransferase, and cholesterol at 42 days). The mineral deposits in the chicken meat were measured for Mg, Fe, Ca, Na, J, and total N. The fifth treatment had a significantly higher glycogen ratio (p < 0.05). pH measurements for the thigh and breast were done immediately, 4, 12, and 24 h after slaughter. For the thigh, the seventh treatment was highest immediately and at 12 h. For the breast, significant differences were only noted at 12 h for chickens on a coriander diet. Conclusion: It is concluded that these additives have a positive effect on some of the blood profiles, carcass characteristics, and mineral composition of chicken meat. J. Adv. Vet. Anim. Res., 6(1): 33-43, March 2019